The Reality of External Auditing in The Company - Ammar, LAID (My University, 2022)
This study is about the reality of external auditing in the company, using a case of EURL MIK “Maintenance industrielle kadda”. The case study method was chosen to provide a general image on how the company practices auditing as an example of a private company in Algeria. Inductive approach was adopted in this study by using historical events and tools in the theoretical side and statistical tools in the practical. The Study reveals that the external auditor plays a very big and important role in ensuring that the companies and the company MIK complies with financial reporting and law standards. And as a result the study results will help the financial managers or other students understand what really is external auditing and how the final general report of the external auditor about the company is made.
Case Study: EURL MIK “Maintenance Industrielle Kadda”
Keywords: external auditing, company, management, performance, organization, control